1998
DOI: 10.1046/j.1365-2362.1998.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of peptide YY and inhibition of gastric acid secretion by long‐chain and medium‐chain triglycerides but not by sucrose polyester in men

Abstract: We speculate that peptide YY may play an important role in the inhibition of gastrin-stimulated gastric acid secretion by long-chain and medium-chain triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…35 The infusion of fat into the duodenum also induces a duodenal brake 18. These effects are probably due to the stimulation of specialised mucosal cells such as I cells of the duodenojejunum that secrete cholecystokinin,2 31 34 or due to the release of peptide YY,36 both of which can delay gastric emptying. Thus, the prolonged colonic motor response that is induced by a fat meal may in part be due to the slower transit of this meal through the upper gut and the release of cholecystokinin 31…”
Section: Discussionmentioning
confidence: 99%
“…35 The infusion of fat into the duodenum also induces a duodenal brake 18. These effects are probably due to the stimulation of specialised mucosal cells such as I cells of the duodenojejunum that secrete cholecystokinin,2 31 34 or due to the release of peptide YY,36 both of which can delay gastric emptying. Thus, the prolonged colonic motor response that is induced by a fat meal may in part be due to the slower transit of this meal through the upper gut and the release of cholecystokinin 31…”
Section: Discussionmentioning
confidence: 99%
“…PYY was measured in plasma by a sensitive and specific radioimmunoassay [35, 36]. The detection limit of the assay was obtained at a final concentration in the incubation mixture of 0.3 p M PYY and the ID 50 at 1.7 p M .…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study we found a strong correlation between increments of PYY in plasma and inhibition of gastrinstimulated gastric acid secretion by intraduodenal administration of dietary fat (17). The aim of this study was to further establish the role of circulating PYY in the inhibition of gastrin-stimulated gastric acid secretion by dietary fat.…”
mentioning
confidence: 86%
“…The amount of acid secreted (mmol/15 min) was calculated as follows: (acid concentration measured Á V A )/recovery. PYY and gastrin concentrations in plasma were measured with sensitive and specific radioimmunoassays as previously described (17,21). Study 2.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation